The CD38+HLA-DR+ T cells with activation and exhaustion characteristics as predictors of severity and mortality in COVID-19 patients - Long, Qiuyue; Song, Shixu; Xue, Jianbo; Yu, Wenyi; Zheng, Yaolin; Li, Jiwei; Wu, Jing; Hu, Xiaoyi; Jiang, Mingzheng; Ye, Hongli; Zheng, Binghan; Wang, Minghui; et al. (Frontiers in Immunology, 2025)
BackgroundThe COVID-19 pandemic remains a global health challenge. Severe cases often respond poorly to standard treatments, highlighting the necessity for novel therapeutic targets and early predictive biomarkers.MethodsWe utilized flow cytometry to analyze peripheral immune cells from healthy, bacterial pneumonia patients, and COVID-19 patients. The expansion of activated T cells (CD38+HLA-DR+), monocytes, and myeloid-derived suppressor cells (MDSCs) were detected and correlated with clinical outcomes to evaluate prognostic potential. The single-cell RNA sequencing (scRNA-seq) was applied to characterize the critical cell subset associated with prognosis and elucidate its phenotype in COVID-19.ResultsWe revealed a significant increase in CD38+HLA-DR+ T cells in non-survivor COVID-19 patients, establishing them as an independent risk factor for 28-day mortality. The scRNA-seq analysis identified the CD38+HLA-DR+ T cell as a terminally differentiated, Treg-like subset exhibiting both activation and exhaustion characteristics. This subset presented the highest IL-6 and IL-10 mRNA levels among all T-cell subsets. Further functional analysis demonstrated its enhanced major histocompatibility complex class II (MHC-II) cross-signaling and correspondingly enriched cytoskeletal rearrangement processes. In addition, there was dysregulated NAD+ metabolism in CD38+HLA-DR+ T cells via scRNA-seq, accompanied by elevated adenosine and decreased NAD+ levels in serums from COVID-19 patients.ConclusionsWe identified the selective expansion of CD38+HLA-DR+ T cells as a novel prognostic indicator for COVID-19 outcomes. These cells’ unique activated-exhausted phenotype, along with their impact on NAD+ metabolism, provides new insights into COVID-19 immunopathogenesis.